Novel technologies in agriculture, food safety and nutrition can pregnant women improve food diversity: Experience from Maternal Nutrition Intervention Project. - Islam, Monirul. (Tufts University. Tisch Library., 2019)
This poster identifies novel technologies in agriculture, food safety and nutrition can pregnant women improve food diversity. Experience from maternal nutrition intervention project.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy